2012
DOI: 10.1542/peds.2012-0021
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Explicit Cell Phone Messaging Associated With Sexual Risk Among Adolescents

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Sending and receiving sexually explicit picture and text messages via cell phone (ie, "sexting") among adolescents is publicized as a societal and public health concern, yet it is unknown whether sexting is associated with physical sexual activity or sexual risk behavior. WHAT THIS STUDY ADDS:This study is the first to examine sexting among a probability sample of adolescents and found that sexting is associated with sexual activity, sexual risk behavior, and knowing other person(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
206
4
20

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 218 publications
(251 citation statements)
references
References 14 publications
20
206
4
20
Order By: Relevance
“…For example, teenagers who had sexted were 5 times as likely to have had vaginal sex, putting them at greater risk for pregnancy or sexually transmitted infections. ARTICLE Consistent with previous literature, 6 sexting was also associated with same-sex sexual behaviors (making out, touching genitals). In short, sexting appears to co-occur with sexual behaviors and may represent an indicator of sexual risk.…”
Section: Discussionsupporting
confidence: 88%
“…For example, teenagers who had sexted were 5 times as likely to have had vaginal sex, putting them at greater risk for pregnancy or sexually transmitted infections. ARTICLE Consistent with previous literature, 6 sexting was also associated with same-sex sexual behaviors (making out, touching genitals). In short, sexting appears to co-occur with sexual behaviors and may represent an indicator of sexual risk.…”
Section: Discussionsupporting
confidence: 88%
“…Rice and colleagues found that teenagers who sexted were 7 times more likely to be sexually active and nearly twice as likely to engage in unprotected sex than their peers. 6 Similarly, a study by Temple and colleagues found 10th and 11th graders who sexted were more likely to have had sex. They also found that girls who had sent naked photos of themselves had a higher chance of engaging in risky sex, including having multiple partners and using substances before sex.…”
mentioning
confidence: 95%
“…5 To date only 1 study has examined the relationship of sexually explicit messages and photos with sexual behavior. 6 However, because sending messages and photos were measured as 1 item, the authors could not assess the equivalence of these 2 behaviors. This distinction may be important because sending a sexually explicit message may not have the same social consequences as sending a photo.…”
mentioning
confidence: 99%
See 2 more Smart Citations